The Effects of Network Architecture on the Photomechanical Performance of Azo-Acrylate Liquid Crystal Elastomers - Anastasiia Svanidze; Sudarshan Kundu; Olena Iadlovska; Anil K. Thakur; Xiaoyu Zheng; Peter Palffy-Muhoray (Crystals)
Azo-containing liquid crystal elastomers are photomechanical materials that can be actuated via illumination. The photomechanical response is a result of the photoisomerization of the azo moiety, which produces bulk stresses in the material. These stresses arise via two distinct and competing mechanisms: order parameter change induced stress and direct contractile stress. We describe thermomechanical and photomechanical experiments aimed at assessing the relative contributions of these. We show that the details of the attachment of azo dyes to the network can greatly influence the photoresponse. We discuss our results and summarize our findings.